Non‐invasive tragus stimulation improves cardiac post‐ischemic remodeling by regulating cardiac parasympathetic activity - Mingxian Chen; Hui Chen; Zhen Wang; Yuchen Pan; Huihui Hu; Songyun Wang; Yuan Yuan; Zhuo Wang; Hong Jiang (ESC Heart Failure, 2022)
Abstract Aims Our previous study proved that low‐level tragus nerve stimulation (LL‐TS) could improve left ventricular remodelling by cardiac down‐stream mechanisms. However, the cardiac up‐stream mechanisms remain unknown. Methods and results Twenty‐eight adult beagle dogs were randomly divided into an MI group (myocardial infarction was induced by permanent ligation of the left coronary artery, n = 10), an LL‐TS group (MI plus intermittent LL‐TS treatment, n = 10), and a control group (sham ligation with the same stimulation as the LL‐TS group, n = 8). Auricular tragus nerve was bilaterally delivered to the tragus via ear‐clips connected to a custom‐made stimulator. The voltage slowing sinus rate was used as the threshold to set the LL‐TS 80% below this level. At the end of 4 weeks post‐MI, LL‐TS could significantly increase atrial ganglion plex (GP) activity, decreased left stellate ganglion (LSG) activity, reduced LV dilation, and improved ventricular functions. Chronic intermittent LL‐TS treatment significantly attenuated left ventricular remodelling via the up‐regulation of α7nAChR expression and the down‐regulation of MMP‐9 level in post‐MI LV tissue. The elevated protein and mRNA of MMP‐9 levels in remote areas were significantly ameliorated by LL‐TS treatment. Conclusions Chronic LL‐TS increased GP neural activity and improved ventricular remodelling possibly via α7nAChR/MMP‐9 axis.